Analysis the Concept of Social Justice from Perspective in Tafseer Al-Munir - Saudiah, Paridatus; Yusrial, Yusrial; Putri, Mirna; Rahmanda, Rega; Ardianda, Viona; Samsurizal, Samsurizal; Ediz, M.Hidayat (UKAZ: International Journal of Islamic Studies, 2024)
Social justice is an ideal that everyone hopes for. The Quran has ordered to uphold justice in every aspect of life. Therefore, this article will discuss the concept of social justice and then relate it to the Quran so that it can be understood and applied in life. The existence of this research can minimize the occurrence of social conflicts in society, especially those related to justice. This research uses a qualitative method with a thematic analysis approach, the data source obtained from the tafseer Al-Munir, then collects secondary sources by reviewing the sources; from books, theses, journals, articles and papers related to the concept of human justice. Then analyzed thematically based on the explanations contained in the interpretive tafseer of the mufassir. Furthermore, to strengthen the analysis and discussion the author also refers to books, expert opinions and various findings from previous researchers related to this issue and topic. The analysis findings found that justice is not only focused on individual interactions with society, but also interactions between individuals and the Khaliq community and themselves. Damage to justice in one of these elements will create new problems in a person's life. That the concept of justice in the Quran is in accordance with the interpretation interpreted by Wahbah Az-Zuhaili. Apart from that, justice contained in Surah An-Nisa verse 135 regarding the concept of social justice contained in the Quran and the interpretation of Wahbah Az-Zuhaili is upholding justice and working together to help each other, prohibiting taking sides with one party in giving testimony.